Analysis of Service Preferences for NTC and NCELL Among Students and Parents at Myanglung Campus, Tehrathum - Dahal, Shiba Prasad (Intellectual Journal of Academic Research, 2024)
This study examines the usage patterns, preferences, and satisfaction levels of Nepal Telecom (NTC) and NCELL services among students and parents at Myanglung Campus, Tehrathum, Nepal. A mixed-methods approach was employed, utilizing both surveys and interviews to collect comprehensive data. A total of 176 participants were included in the study, comprising 88 students and 88 parents, selected through convenience sampling. Data were gathered using structured questionnaires and semi-structured interviews to explore mobile usage patterns, satisfaction levels, and factors influencing mobile operator choice. Quantitative data were analyzed using statistical methods, while qualitative data were examined for recurring themes. The results indicate distinct preferences between students and parents. Students exhibit a strong preference for data services and promotional offers, reflecting their digital lifestyle and need for constant connectivity. They are more critical of customer service, with many expressing neutral or dissatisfied sentiments. Conversely, parents prioritize network coverage and customer service, valuing reliable communication channels and traditional voice services. Parents generally report higher satisfaction levels, potentially due to their lower expectations regarding data speed and innovation. Both groups agree on the importance of network coverage and service quality, albeit with varying degrees of emphasis. This study contributes to the understanding of mobile telecommunications preferences in a rural and semi-urban context in Nepal, providing valuable insights for service providers and policymakers to improve telecommunications services and customer satisfaction. Keywords: NTC, NCELL, mobile telecommunications, service preference, students, parents, Myanglung Campus